Modeling short QT syndrome using human‐induced pluripotent stem cell-derived cardiomyocytes - El-Battrawy, Ibrahim; Lan, Huan; Zhao, Zhihan; Buljubasic, Fanis; Lang, Siegfried; Yücel, Gökhan; Sattler, Katherine; Utikal, Jochen; Wieland, Thomas; Borggrefe, Martin; Zhou, Xiao-Bo; Akın, Ibrahim (Journal of the American Heart Association, 2018)
BackgroundShort QT syndrome (SQTS), a disorder associated with characteristic ECG QT‐segment abbreviation, predisposes affected patients to sudden cardiac death. Despite some progress in assessing the organ‐level pathophysiology and genetic changes of the disorder, the understanding of the human cellular phenotype and discovering of an optimal therapy has lagged because of a lack of appropriate human cellular models of the disorder. The objective of this study was to establish a cellular model of SQTS using human‐induced pluripotent stem cell-derived cardiomyocytes (hiPSC‐CMs).Methods and ResultsThis study recruited 1 patient with short QT syndrome type 1 carrying a mutation (N588K) in KCNH2 as well as 2 healthy control subjects. We generated hiPSCs from their skin fibroblasts, and differentiated hiPSCs into cardiomyocytes (hiPSC‐CMs) for physiological and pharmacological studies. The hiPSC‐CMs from the patient showed increased rapidly activating delayed rectifier potassium channel current (IKr) density and shortened action potential duration compared with healthy control hiPSC‐CMs. Furthermore, they demonstrated abnormal calcium transients and rhythmic activities. Carbachol increased the arrhythmic events in SQTS but not in control cells. Gene and protein expression profiling showed increased KCNH2 expression in SQTS cells. Quinidine but not sotalol or metoprolol prolonged the action potential duration and abolished arrhythmic activity induced by carbachol.ConclusionsPatient‐specific hiPSC‐CMs are able to recapitulate single‐cell phenotype features of SQTS and provide novel opportunities to further elucidate the cellular disease mechanism and test drug effects.